Improving the power factor correction in the presence of harmonics by reducing the effect of resonance and harmonics - Saber M. Saleh; Mohamed E. Arafa (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Harmonics in electrical networks occur as a result of non-linear loads.  It has an effect on power factor improvement using capacitors in terms of increasing the unbalance current between units. In addition, the occurrence of resonance and result in the exit of capacitors from service by the protective relays to protect the units from collapse. The main objective of this research is the real-time study of improving the power factor with reducing the effect of the resonance and harmonics on the power system. This reduction can be done using filters, consist of reactors and capacitors connected in series or in parallel or series and parallel together to reduce the current harmonics or voltage harmonics. Single Tuned filter type (passive filter) is used which presents very low impedance at the tuning frequency, through which all current of that particular frequency will be diverted. This research presents two practical power systems 11kV source in Fayoum substation and 13.8kV source in New Badr substation connected to power factor Improvement circuit. These models simulated by Matlab at different unbalance currents and harmonics. Also, it presents the design of the series reactor and the harmonics filter which satisfy the minimum effect of resonance and harmonics.